An Overview of Management of Root Fractures - Prithviraj, DR; Balla, HK; Vashisht, R; Regish, KM; Suresh, P (Kathmandu University Medical Journal, 2015)
Crown or root fractures are the most commonly encountered emergencies in the dental clinic. Root fractures occur in fewer than eight percent of the traumatic injuries to permanent teeth. They are broadly classified as horizontal and vertical root fractures. Correct diagnosis of root fractures is essential to ensure a proper treatment plan and hence, the best possible prognosis. Indication of the type of treatment to be used depends primarily on the level of the fracture line. Therefore, a clinician must also have a thorough knowledge of the various treatment approaches to devise a treatment plan accordingly. Various treatment strategies have been proposed, each with their own advantages and disadvantages. Hence, this literature review presents an overview of the various types of root fractures and their management. Kathmandu University Medical Journal Vol.12(3) 2014; 222-230